Ventral hernia repair with enhanced-view totally extraperitoneal technique after a massive weight loss by laparoscopic sleeve gastrectomy - Manabu Amiki; Yasuhiro Ishiyama; Ichitaro Mochizuki; Kazuhiro Narita; Manabu Goto; Koji Sekikawa (Surgical Case Reports, 2023)
Abstract Background Ventral hernia repair (VHR) for obese patients is often associated with an increased risk of postoperative complications and hernia recurrences. Achieving preoperative weight loss is ideal before VHR; however, it is difficult to attain with medical treatment. Metabolic and bariatric surgery (MBS) offers the most effective and durable treatment for obesity. Therefore, massive weight loss occurring after MBS will improve the outcome of VHR. Case presentation A 49-year-old man (122.9 kg, BMI 39.1 kg/m2) presented to our hospital wishing to undergo laparoscopic sleeve gastrectomy and VHR. Physical examination revealed a tennis ball-sized lower midline defect. Computed tomography (CT) scans revealed a hernia orifice 5 cm in width and 10 cm in height. As the hernia orifice was large, mesh reinforcement was essential. We planned for him to undergo VHR after massive weight loss was achieved by MBS. VHR was performed using the enhanced-view totally extraperitoneal (eTEP) technique after weight loss of 38 kg was achieved 9 months following laparoscopic sleeve gastrectomy. His postoperative course was uneventful, and neither recurrence nor seroma was observed at 1 year follow-up. Conclusions eTEP repair of a ventral hernia after massive weight loss following MBS would appear to be the best combination treatment for obese patients with ventral hernias. However, long-term follow-up is necessary to establish its safety and efficacy.